Objective Outcomes of Closed Reduction According to the Type of Nasal Bone Fracture - Kang, Chang Min; Han, Dong Gil (Archives of craniofacial surgery, 2017)
Nasal fractures have a tendency of resulting in structural or functional complications, and the results can vary according to the type of nasal bone fracture. The aim of this study was to evaluate the objective postoperative results according to the type of nasal bone fractures. We reviewed 313 patients who had a closed reduction of nasal bone fracture. The classification of nasal bone fracture by Stranc and Robertson was used to characterize the fracture type: frontal impact group type I (FI), frontal impact group type II (FII), lateral impact group type I (LI), lateral impact group type II (LII), and comminuted fracture group (C). For each patient, we tried to use the same axial image section of computed tomographic (CT) scans before and immediately after operation. Postoperative outcomes were classified into 4 grades: excellent (E), good (G), fair (F), and poor (P). We also analyzed postoperative complications by fracture type. Regarding the postoperative CT images, 189 subjects showed E results, 99 subjects showed G, 18 subjects showed F, and 7 subjects showed P reduction. The rate of operation results graded as E by each fracture type was 66.67% in FI, 52.0% in FII, 64.21% in LI, 62.79% in LII, and 21.74% in C. Complications of FI (7.14%), LII (13.95%), and C (13.04%) groups occurred more than in the FII (4.00%) and LI (4.21%) groups. It seems that the operation result by fracture type was better in the FI, LI, and LII type than the FII and C type; after one month, however, LII type showed more complications than other types. The septal fracture can be thought to affect early reduction results in nasal bone fractures.